(untitled) (Perner’s Contacts, 2016)
The contribution deals with increasing of the transport safety in light-controlled intersections in connection with the vehicles with preferential rights of ride. The authors of contribution propose possibilities for implementation of the system of intelligent signalling device RMS2, description of technical parameters and operating principle.